Biocompatible Multifunctional Black‐Silicon for Implantable Intraocular Sensor. Issue 4 (12th January 2017) - Lee, Jeong Oen; Narasimhan, Vinayak; Du, Juan; Ndjamen, Blaise; Sretavan, David; Choo, Hyuck
Abstract : Multifunctional black‐silicon (b‐Si) integrated on the surface of an implantable intraocular pressure sensor significantly improves sensor performance and reliability in six‐month in vivo studies. The antireflective properties of b‐Si triples the signal‐to‐noise ratio and increases the optical readout distance to a clinically viable 12 cm. Tissue growth and inflammation response on the sensor is suppressed demonstrating desirable anti‐biofouling properties.